Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja dan Employee Well Being terhadap Turnover Intention Karyawan pada PT Sumber Masanda Jaya (Studi pada Bagian Assembling Gedung UP1) - Faiz Irsyad Prasetyo; Muhammad Siddik Erdi Wicaksono; Safira Aulia Hasan; Zhahra Adelia; Anis Mamluatul Inayah; Riska Ajeng Putri (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
The high rate of employee turnover has become a significant challenge for many companies, as it can disrupt operational stability and potentially reduce the morale and motivation of employees who remain. PT Sumber Masanda Jaya is a large manufacturing company operating in the sports footwear industry. The company produces various shoe models with world-class or international quality under the Nike brand. This study aims to analyze the effect of transformational leadership style, work environment, and employee well-being on employee turnover intention at PT Sumber Masanda Jaya, focusing on the assembling division of Building UP 1. The research employed a quantitative approach using multiple linear regression analysis on 94 respondents selected through convenience sampling. The results show that partially, transformational leadership does not have a significant effect on turnover intention. The work environment has a negative and significant effect, indicating that a conducive work environment can reduce employees’ intention to leave the company. Conversely, employee well-being has a positive and significant effect on turnover intention, suggesting that employees with higher levels of well-being may have a greater tendency to seek broader career opportunities. Simultaneously, the three independent variables significantly influence turnover intention. This study emphasizes the importance of organizations in creating a supportive work environment and understanding employee well-being dynamics to manage turnover risks more effectively.